The Symbols of Anxiety in Rumaan Alam’s “Leave The World Behind” - Ridho Pratama Satria; Wilma Prafitri; Fatimah Muhajir (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research examines the meanings of the symbols appearing in Rumaan Alam's novel